Ecogeography and utility to plant breeding of the crop wild relatives of sunflower (Helianthus annuus L.) - Kantar, Michael B.; Sosa, Chrystian C.; Khoury, Colin K.; Castañeda-Álvarez, Nora P.; Achicanoy, Harold A.; Bernau, Vivian; Kane, Nolan C.; Marek, Laura; Seiler, Gerald; Rieseberg, Loren H. (Frontiers in Plant Science, 2015)
Crop wild relatives (CWR) are a rich source of genetic diversity for crop improvement. Combining ecogeographic and phylogenetic techniques can inform both conservation and breeding. Geographic occurrence, bioclimatic, and biophysical data were used to predict species distributions, range overlap and niche occupancy in 36 taxa closely related to sunflower (Helianthus annuus L.). Taxa lacking comprehensive ex situ conservation were identified. The predicted distributions for 36 Helianthus taxa identified substantial range overlap and asymmetry and niche conservatism. Specific taxa (e.g., Helianthus deblis Nutt., Helianthus anomalus Blake, and Helianthus divaricatus L.) were identified as targets for traits of interest, particularly for abiotic stress tolerance and adaptation to extreme soil properties. The combination of techniques demonstrates the potential for publicly available ecogeographic and phylogenetic data to facilitate the identification of possible sources of abiotic stress traits for plant breeding programs. Much of the primary genepool (wild H. annuus) occurs in extreme environments indicating that introgression of targeted traits may be relatively straightforward. Sister taxa in Helianthus have greater range overlap than more distantly related taxa within the genus. This adds to a growing body of literature suggesting that in plants (unlike some animal groups), geographic isolation may not be necessary for speciation.